The role of leadership in promoting quality management: a study on the Chittagong City Corporation, Bangladesh - Quddus, S. M. Abdul; Ahmed, Nisar Uddin (IIUM Press, International Islamic University Malaysia, 2017)
Leadership plays a crucial role in ensuring quality management in an organization. The purpose of this article is to examine the roles of leadership in quality management relating to the Chittagong City Corporation (CCC), one of the major urban government units in Bangladesh. This study is guided by the European Foundation of Quality Management (EFQM) model, which is a quality assessment tool designed to evaluate an organization’s quality management capacity. This paper will focus on the role of leadership because it is one of the major “enabler” components of the EFQM model for quality management. When talking about quality management in an organization, leaders develop and facilitate the achievement of the mission and vision of the organization. They also develop organizational values and systems required for sustainable success and implement these via their actions and behaviours. In relation to this study, both quantitative and qualitative data collection methods were used to gather and analyse that information. Quantitative data were collected from a total of 142 participants, including selective Chittagong City Corporation officials, city inhabitants, government officials and NGO and civil society personnel by using a structured questionnaire. The findings of this study reveal that the CCC leadership has played a positive role in their interaction with the customers, partners and representatives of society. Data also revealed that the leaders of CCC reinforce a culture of improvement in their support of staff and they tend to identify and promote organizational change. However, our data also found that leaders/managers of CCC are not aware of the necessity to develop the mission, vision, values and ethics of quality management in the organization and they lack the quality or capacity to be a proper role model for a culture of excellence, even though they are personally involved in the development, implementation and continuous improvement process of the CCC. This study suggests that the leaders/managers of CCC need to develop a properly structured organizational mission, vision, value framework and system that is essential to improve the quality of management in the organization.